Promoting Women in Physics and Astronomy Through a Public Lecture Series at UW-La Crosse - Lesher, Shelly R. (Proceedings of the Wisconsin Space Conference, 2015)
Undergraduate women in the Physics Department at UW- La Crosse form a small percentage of majors and are spread out across years and among sub-programs. In addition, they may encounter few women scientist during their undergraduate career. As a result, they can feel isolated and uncertain about careers in their chosen fields. A women speaker was brought to UW – La Crosse to serve as a role model for undergraduate women in the physics program and to expose them to career opportunities in a space-related field. The speaker gave an interdisciplinary science seminar, a physics specific lecture, and met with students over lunch in small group discussion. Student feedback was very positive, and the visit increased the exposure to the different careers women, and all students, could have in science.